BIOCLIMATIC STRATEGIES FOR THE CITY OF LAJEADO/RS-BRAZIL, USING DATA ANALYSIS OF REGIONAL CLIMATE - Spinelli, Rodrigo; Konrad, Odorico; Cambeiro, Faustino Patiño; Ahlert, Edson; Spinelli, Fabiana Braun; Quadros, Eric Augusto (Revista Brasileira de Climatologia, 2021)
The city of Lajeado is located at the Vale do Taquari region, 120 km away from Porto Alegre, the capital of Rio Grande do Sul (RS) state, Brazil. Locally, the civil construction industry has grown 517.7% between the years of 1991 and 2011. Basic information concerning the choice of materials suitable to the climate, and early studies focused on the research of natural ventilation, are denied in the development of projects of buildings. Bioclimatic Charts are being developed for Brazil, in which architectural strategies can be determined for application in building project design. The study here shown is about acquisition of climate data for the city of Lajeado in southern of Brazil, during the period of 2004 to 2015, including data processing and analysis using BioEstat statistic software and data plotting to the bioclimatic chart with the use of the Sol-ar software. The results show how building design strategies like passive solar heating and thermal inertia, as well as an adequate application of construction materials, must be used more, as to working with thermal isolation in cold and hot days.